Cultural Performance and Religious Nationalism: A Theoretical Model of Value Internalization through Wayang Aji Narantaka - Ahmad Najih Musoffa Fuadi; Naila Intania (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This study examines the role of Wayang Kulit, particularly the Aji Narantaka episode, as a medium for the internalization of religious nationalism within rural communities. The study focuses on a community service program conducted in Temengeng Village, Blora Regency, where wayang performances had been absent for more than a decade despite previously functioning as an important collective cultural tradition. Guided by the Religious-Cultural Nationalism Internalization (RCNI) Model, this study employed the Participatory Action Research (PAR) approach involving community leaders, local residents, village officials, audience participants, and the university service team. Data were collected through participatory observation, semi-structured interviews, and documentation, and were analyzed qualitatively through thematic interpretation. The findings reveal that the revitalization of the wayang performance strengthened cultural loyalty, collective solidarity, moral-religious responsibility, and community commitment toward sustaining local cultural traditions. The symbolic values embodied in the Aji Narantaka episode also fostered emotional engagement and collective awareness regarding social responsibility, cultural preservation, and national identity. These findings demonstrate that traditional cultural performances can function not only as cultural preservation activities, but also as a form of social pedagogy capable of strengthening religious nationalism through collective cultural experiences in rural community life.